Muscle Tone Physiology and Abnormalities - Jacky Ganguly; Dinkar Kulshreshtha; Mohammed Almotiri; Mandar Jog (Toxins, 2021)
The simple definition of tone as the resistance to passive stretch is physiologically a complex interlaced network encompassing neural circuits in the brain, spinal cord, and muscle spindle. Disorders of muscle tone can arise from dysfunction in these pathways and manifest as hypertonia or hypotonia. The loss of supraspinal control mechanisms gives rise to hypertonia, resulting in spasticity or rigidity. On the other hand, dystonia and paratonia also manifest as abnormalities of muscle tone, but arise more due to the network dysfunction between the basal ganglia and the thalamo-cerebello-cortical connections. In this review, we have discussed the normal homeostatic mechanisms maintaining tone and the pathophysiology of spasticity and rigidity with its anatomical correlates. Thereafter, we have also highlighted the phenomenon of network dysfunction, cortical disinhibition, and neuroplastic alterations giving rise to dystonia and paratonia.